1987
DOI: 10.1046/j.1537-2995.1987.27487264743.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein changes occurring during storage of platelet concentrates

Abstract: The changes in thrombocyte proteins during 22 degrees C storage of platelet concentrates (PC) were studied. To prepare a reference protein "map" of stored PC, platelet samples were taken on days 1, 7, and 21. The platelet proteins were separated by isoelectric focusing (first-dimension) followed by second-dimension polyacrylamide gradient gel electrophoresis with sodium dodecylsulfate (2D). The silver-stained gels were analyzed by computer to obtain a composite map of stored PC proteins. The pattern seen on da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Indeed, several pre-analytical factors may modify platelet structure and function and consequently the final proteomic profile. These factors include the recent administration of drugs interfering with platelet function such as aspirin or non-steroid anti-inflammatory drugs (Patrono & Rocca, 2009), quick isolation of platelets after blood collection (Thon, Schubert, & Devine, 2008a) or, in case of platelet concentrate bags, their storage (Snyder et al, 1987) and age (Egidi et al, 2010) and temperature of the platelet suspension (ideally at 378C) These isolation features may induce protein modifications, such as glycosylations (Wandall et al, 2008), and thus bias the results. This is of high importance when platelets are isolated from medical blood transfusion products.…”
Section: A Platelet Isolationmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, several pre-analytical factors may modify platelet structure and function and consequently the final proteomic profile. These factors include the recent administration of drugs interfering with platelet function such as aspirin or non-steroid anti-inflammatory drugs (Patrono & Rocca, 2009), quick isolation of platelets after blood collection (Thon, Schubert, & Devine, 2008a) or, in case of platelet concentrate bags, their storage (Snyder et al, 1987) and age (Egidi et al, 2010) and temperature of the platelet suspension (ideally at 378C) These isolation features may induce protein modifications, such as glycosylations (Wandall et al, 2008), and thus bias the results. This is of high importance when platelets are isolated from medical blood transfusion products.…”
Section: A Platelet Isolationmentioning
confidence: 99%
“…Indeed, apheresis or whole blood units used in research settings are usually out-ofdate. In these conditions, storage duration or temperature are not driven by the experimental workflow, but by transfusion guidelines and preliminary tests should be done to ensure the quality of the platelet suspension (Snyder et al, 1987;Thon, Schubert, & Devine, 2008a;Thon et al, 2008b). For instance, it has been shown by Hoffmeister et al (2003a,b) that cooling platelets induces a rapid clearance of the platelets, which can be of high importance in case of transfusion, but also for platelet functional studies from medical blood product.…”
Section: A Platelet Isolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein analysis of platelets during storage was first achieved in the end of the 1980s by identifying variation in actin [56,57]. However, actin polymerization is linked to the method used in the preparation of PCs and it has been shown that this process is partially reversible after 1 day of storage [58], which is highlighting the implication of pre-analytics in biomarker discovery.…”
Section: Analysis Of Blood Products Aging and Storage Lesions Biomarkmentioning
confidence: 99%
“…modifications of platelet proteins due to storage were de scribed using the two-dimensional polyacrylamide gel electrophoresis (2D-PAGE) [22], In this study we compared non-filtered platelet concen trates (NFPCs) and filtered platelet concentrates (FPCs) during a storage period of 7 days. GPIb, GPIIb/IIIA and GMP-140 platelet surface expression was assessed using specific monoclonal antibodies (MoAb) and flow cytom etry, platelet responses to thrombin and ristocetin were studied by aggregometry and platelet protein patterns were analyzed by 2D-PAGE.…”
mentioning
confidence: 99%